2014
DOI: 10.1016/j.jtcvs.2014.04.004
|View full text |Cite
|
Sign up to set email alerts
|

First nationwide survey of US integrated 6-year cardiothoracic surgical residency program directors

Abstract: Objective The recently implemented integrated 6-year (I-6) format represents a significant change in cardiothoracic surgical residency training. We report the results of the first nationwide survey assessing I-6 program directors' impressions of this new format. Methods A 28-question web-based survey was distributed to program directors of all 24 Accreditation Council for Graduate Medical Education-accredited I-6 training programs in November 2013. The response rate was a robust 67%. Results Compared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 4 publications
(8 reference statements)
1
13
0
Order By: Relevance
“…In the first nationwide survey of I-6 program directors, 75% believed their I-6 graduates would be able to independently perform routine cardiac and thoracic operations by the time of graduation, with this rate increasing to 86% in mature programs. 6 Sixty-seven percent believed I-6 graduates would be ''better trained'' than traditional pathways, although this was not specific to operative preparedness.…”
Section: Discussionmentioning
confidence: 99%
“…In the first nationwide survey of I-6 program directors, 75% believed their I-6 graduates would be able to independently perform routine cardiac and thoracic operations by the time of graduation, with this rate increasing to 86% in mature programs. 6 Sixty-seven percent believed I-6 graduates would be ''better trained'' than traditional pathways, although this was not specific to operative preparedness.…”
Section: Discussionmentioning
confidence: 99%
“…Some other concerns included the unwillingness of the surgical faculty to train such junior residents, and residents' attrition in midcourse. The nationwide surveys indicated that the programs attract and retain highly qualified trainees, with high satisfaction among the program directors [3,4].…”
Section: Commentmentioning
confidence: 99%
“…In a recent survey of residents in the United States who have entered the 6-year integrated program, although 94% considered the time saved in total years of training an advantage, 58% favored a 7-year program for the additional board certification in vascular surgical procedures, or wished to take time off for dedicated research and favored an extra year as a fellowship at the completion of their training [2]. Among the directors of 6-year programs in the United States, 75% believed that their graduates would be able to competently and independently perform routine cardiothoracic operations in adults [4].…”
Section: Commentmentioning
confidence: 99%
“…The external pressures to cardiac surgical training are remarkably consistent to reports from North America, Europe, and Asia. [2][3][4] The major challenges to recruitment represent a combination of (1) the perceived small pool of jobs, (2) low reimbursement, and (3) adequate ''work-life balance.'' Attracting top-class medical students and more women to cardiac surgery is crucial to ensure the continued vitality of our specialty.…”
mentioning
confidence: 99%